Comparison of Serum Lipid Profile in Cirrhotic Versus Non-Cirrhotic Patients with Viral Hepatitis - Rehman, Mehar; Tareen, Tariq Bashir; Malik, Muhammad Umair Ijaz; Malik, Muhammad Uzair Ijaz (Pakistan Armed Forces Medical Journal, 2024)
Objective: To evaluate the association of lipoprotein cholesterol levels in cirrhotic versus non-cirrhotic patients with viral hepatitis.Study Design: Analytical cross-sectional.Place and Duration of Study: Department of General Medicine, Pakistan Aeronautical Complex Hospital, Kamra Pakistan, from Feb to Aug 2021.Methodology: Our study included patients presenting to medical OPD with diagnosed chronic viral hepatitis, belonging to either gender and aged between 35 to 75 years. We collected data on a data collection tool regarding basic demographics (age, gender, weight, and etiology of viral hepatitis) and presence of cirrhosis amongst the chronic hepatitis patients was documented. We categorized patients into cirrhotic and non-cirrhotic groups where mean serum lipid levels were noted for comparison.Results: Out of total 100 patients, mean age of the patients was 56.01±8.46 years. The mean serum cholesterol, LDL (low-density lipoprotein), HDL (high-density lipoprotein), and triglyceride levels were 143.78±26.34 mg/dL, 88.73±17.89 mg/dL, 34.94±7.87 mg/dL, and 100.32±19.18 mg/dL, respectively. A significant difference in serum cholesterol (p-value=0.0002), LDL (p-value=0.0006), HDL (p-value=0.004) and triglyceride level (p-value=0.004) was noted between cirrhotic and non-cirrhotic patients.Conclusion: A significant difference of serum cholesterol, LDL, HDL, and triglyceride level was noted in between cirrhotic and non-cirrhotic patients.